Visualisation technology in digital intelligent warehouse management system. (2nd December 2021) - Tang, Guang Hai; Zeng, Hui
This study introduces visualisation technology into digital intelligent warehouse management, combines Radio Frequency Identification (RFID) technology and Web Geographic Information System (GIS) technology, proposes software architecture, designs database and finally designs a set of intelligent warehouse management system based on visualisation technology. Through the pressure and performance test of the system, it is found that the user's waiting time is shorter, the system performance is stable and the designed system can meet the needs of business operations. By comparing the cost and time of goods storage management in one week, the results show that the system can reduce the cost of storage management by up to 40.3%, reduce the time of management by nearly half, and greatly improve the management efficiency. At the same time, due to the use of intelligent information tools, it can also reduce the mistakes caused by manual operation, improve the competitiveness of enterprises.